Variabilidade espacial e tamanho de parcela em experimentos com culturas olerícolas - Santos, Daniel (2013)
The study aimed to test the efficiency of the method Papadakis on increasing the quality of experiments with snap beans, zucchini, peppers and lettuce, and having efficiency, determine how to estimate the covariate and plot size for use in experiments where apply the method. The definition of the form of estimated covariate that provides greater efficiency and calculation method Papadakis plot size adjusted for use in this method were made from the following blank experiments: two experiments with zucchini, lettuce with eight, five-bean pod and two peppers. In experiments with zucchini, pole beans and peppers, the variable was the weight of fruits and lettuce in experiments with variable mass was fresh shoot. The effectiveness of the use of analysis of covariance (ANCOVA) with the covariate estimated by Papadakis was tested from treatment experiments: one with the bell pepper crop, where the variable was the weight of fruit and one with lettuce crop where the variable was the fresh weight of shoots. The use of ANCOVA with the covariate estimated by Papadakis increases the quality of experiments with vegetable crops. The covariate that provides the highest efficiency ANCOVA is that which is determined considering a portion neighboring each side of the reference portion towards the row of plants. The plot size in the crop row, adjusted for method, is 10 plants (2.0 m) for snap beans, five plants (4.5 m) to zucchini, five plants (1.5 m ) for chili, and four plants (1.2 m) for lettuce.